Development of a new vesicular formulation for delivery of Ifosfamide: Evidence from in vitro, in vivo, and in silico experiments - Mohammad Reza Hajinezhad; Sheida Shahraki; Zahra Nikfarjam; Fatemeh Davodabadi; Shekoufeh Mirinejad; Abbas Rahdar; Saman Sargazi; Mahmood Barani (Arabian Journal of Chemistry, 2023)
Ifosfamide (IFO) is a member of the oxazaphosphorine family of alkylating drugs that exhibits anticancer and immunoregulatory properties. The toxicity of IFO is dose-limited because of its biotransformation into highly reactive metabolites, including acrolein and chloroacetaldehyde. Here, we aimed to design novel niosomal formulations to encapsulate IFO within niosomes and assess the efficacy of the nanoformulation via conducting in vivo, in vitro, and in silico analyses. Niosomal IFO showed a monodisperse size distribution with an average size of 97 nm. In addition, transmission electron microscopy (TEM) revealed a spherical morphology with high stability and no aggregation. On the other hand, niosomal IFO (0.01–100 µg/mL) showed high cytotoxicity against breast cancer (MCF7) and neuroblastoma (SH-SY5Y) cells in a concentration-dependent fashion. IFO-loaded niosomes had lower IC50s in cancerous cell lines than the standard IFO, the most pronounced being in SH-SY5Y cells (IC50 = 0.184 µg/mL). Intravenous treatments of rats with niosomal IFO at 0.1 mg/kg body weight (bw) and 0.2 mg/kg bw significantly increased biochemical parameters such as blood urea nitrogen (BUN), creatinine (CR), alanine aminotransferase (ALT), and aspartate aminotransferase (AST). Moreover, the 0.2 mg/kg bw doses of niosomal IFO caused obvious changes in the liver tissue. Both 0.1 mg/kg bw and 0.2 mg/kg bw doses of free IFO caused histopathological lesions and significantly increased biochemical parameters. In silico calculations revealed the interaction of IFO through its oxygen and nitrogen connected to the phosphor atom and nitrogen with a head group of Span 60 and tween 60. For the first time, we designed a well-characterized niosomal formulation for the targeted delivery of IFO. Our formulation exhibited optimum size with desirable anticancer activity and can be considered a suitable carrier with a high potential for future usage in the controlled release of other chemotherapeutics; however, more studies are needed to assess its safety towards normal human cells.